Three different types of tea as surfactant in liquid exfoliation of graphite : Green tea, black tea and oolong tea - Fadwa Sameeha, Ismail; Kamal, Yusoh; Anis Sakinah, Zainal Abidin; Abu Hannifa, Abdullah; Zulhelmi, Ismail (IOP Publishing Ltd, 2019)
Liquid phase exfoliation (LPE) with surfactant-assisted is a method to produce graphene that used water and surfactant as solvent. Tea is one of possible surfactants that can be used in LPE of graphite as it reduced the surface tension energy of water (72.75 mJ m-2) to ∼40-50 mJ m-2 which is suitable level to exfoliate graphite. Three different types of tea were used as surfactant through one-step production of graphene which were green tea (GT), black tea (BT) and oolong tea (OT). The exfoliation of graphite in each tea solutions were successful as the UV spectra of supernatant samples show peak at 270 nm which indicates the C-C bond of graphene flakes. Morphology analysis (AFM) of resulted graphene samples show that graphene sheets have sharp edges caused by sonication process. The effect of sonication time was being investigated in this work. Green tea has higher exponent factor of time (1.715) compare to black tea (1.033) and oolong tea (0.762) due to high quantity of small molecules of polyphenols present in green tea solution. Thus, it is better to used GT as surfactant in LPE of graphite compare to BT and OT.